Effect of Long Term Oral Warfarin Sodium Treatment on Bone Mineral Density Scores and Spinal Sagittal Alignment - Kamil Eyvazov; Önder Aydemir; Behruz Eyvazov (Galenos Yayinevi, 2016)
Objective: The aim of this study was to investigate the effect of long term oral warfarin sodium treatment on bone mineral density (BMD) and spinal sagittal alignment. Materials and Methods: Sixty four participants were enrolled for this retrospective study. Participants were divided into two groups-participants who had taken warfarin sodium for at least two years (n=33) and participants who had never taken warfarin sodium (n=31). All of the individuals were evaluated at the same center. Dual X-ray absorptiometry (DXA) was used for measuring BMD. Whole spine x-rays were obtained for sagittal assessment and the following parameters were measured: Cervical lordosis, thoracic kyphosis, lumbar lordosis, pelvic incidence, pelvic tilt, sacral slope and sagittal vertical axis (SVA). Results: The mean BMD value was significantly higher in participants who had not taken warfarin sodium compared to participants who had taken warfarin sodium. The differences between the average values were 0.1552 g/cm2 in BMD; 2.1 in T scores; 1.4 in Z scores. On the radiological evaluation of the spine, cervical lordosis was 7.1 degrees lower, lumbar lordosis was 4.7 degrees lower and thoracic kyphosis was 5.3 degrees higher in the patients using drug. C7 plumb line was interchanged forward in the patients using drug. Conclusions: This study shows that warfarin sodium use worsens bone quality in the lumbar region and does not affect bone quality in the femoral region. Furthermore, warfarin sodium use also reduces physiological lordosis and enhances thoracic kyphosis. Consequences of these changes are the likely cause of sagittal spinal anterior imbalance. Long-term oral warfarin sodium use affect bone mineral density and spinal alignment. Our conclusion about giving clear message and show exactly mechanism we need prospective randomized multicentre studies in future. We strongly believe this study will be pioneer for future researches.